A Queer Critique of Psychiatric Knowledge: Medicalising Queer Sadness - Jack, Kate (New Zealand Sociology, 2023)
This article makes a queer critique of psychiatric knowledge based on psychiatry’s use of normal/abnormal categorisations and queer theory’s resistance to such ascriptions. Using the example of the medicalisation of normal sadness seen in increasing major depressive disorder (MDD) diagnoses, it will be argued that so long as its knowledge is grounded in this binary of normal/abnormal, psychiatry can be used to oppress queerness. The article first examines how happiness has become compulsory and articulates this as a normalising process facilitated by psychiatric knowledge. Sadness, as the corresponding abnormal, must and can be cured through psychiatric intervention. Here, psychiatry’s account of increasing MDD diagnoses, especially amongst queer people, is outlined and then deconstructed following a critical account of the medicalisation of sadness. Finally, it draws these points together using queer theory to argue that expectable, socially induced queer sadness represents a double abnormality useful to queer politics but threatening to compulsory happiness as a normalising process. Thus, this sadness must be cured, and by medicalising queer sadness, psychiatry can ‘cure’ both sadness and queerness in the interests of power.